Znaczenie relacji szkoły i rodziny w kontekście budowania wsparcia społecznego rodzin dzieci z niepełnosprawnością w II Rzeczypospolitej Polskiej - Łaga, Patrycja (Biuletyn Historii Wychowania, 2016)
The aim of this paper is to describe and analyse how relationships between school and parents were created in the II RP. The research is based on the analysis of teacher’s articles from “SzkołaSpecjalna” and “PracaSzkolna” in 1925–1939. The author describes the social functioning of families in the II RP. The article also describes how teachers presented their approach to building relationships with their student’s parents, and how this created social support for families, particularly families of children with disabilities.